2019
DOI: 10.1038/s41598-019-48107-2
|View full text |Cite
|
Sign up to set email alerts
|

Label-free assessment of pre-implantation embryo quality by the Fluorescence Lifetime Imaging Microscopy (FLIM)-phasor approach

Abstract: Development of quantitative, safe and rapid techniques for assessing embryo quality provides significant advances in Assisted Reproductive Technologies (ART). Instead of assessing the embryo quality by the standard morphologic evaluation, we apply the phasor-FLIM (Fluorescence Lifetime Imaging Microscopy) method to capture endogenous fluorescent biomarkers of pre-implantation embryos as a non-morphological caliber for embryo quality. Here, we identify, under hypoxic and non-hypoxic conditions, the unique spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
(43 reference statements)
0
32
0
Order By: Relevance
“…This change in signature correlates to a shift towards OXPHOS and GLY, respectively, which has been previously described as the metabolic or M-trajectory [27][28][29][30]. This trajectory has also been shown to correlate with results found in conventional biochemical assays when OXPHOS or GLY inhibitors are used to shift metabolic signatures towards one another [27,[31][32][33]. To ensure the collection of the fluorescence lifetime of NADH, all of the measurements were done using a 2-photon laser excitation set to 740 nm, and the emission was collected with an emission bandpass filter (460/40 nm) to select the emission of NADH.…”
Section: Introductionmentioning
confidence: 64%
“…This change in signature correlates to a shift towards OXPHOS and GLY, respectively, which has been previously described as the metabolic or M-trajectory [27][28][29][30]. This trajectory has also been shown to correlate with results found in conventional biochemical assays when OXPHOS or GLY inhibitors are used to shift metabolic signatures towards one another [27,[31][32][33]. To ensure the collection of the fluorescence lifetime of NADH, all of the measurements were done using a 2-photon laser excitation set to 740 nm, and the emission was collected with an emission bandpass filter (460/40 nm) to select the emission of NADH.…”
Section: Introductionmentioning
confidence: 64%
“…Despite extensive studies and applications of FLIM in metabolic research 1018 , it has been unclear how to relate FLIM measurements to the activities of the underlying metabolic pathways in cells. We overcome this challenge by developing a coarse-grained NADH redox model to relate FLIM measurements to mitochondrial metabolic fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous NADH has long been used to non-invasively probe cellular metabolism because NADH is autofluorescent, while NAD + is not (Heikal, 2010). Fluorescence lifetime imaging microscopy (FLIM) of NADH autofluorescence allows quantitative measurements of the concentration of NADH, the fluorescence lifetimes of NADH, and the fraction of NADH molecules bound to enzymes (Becker, 2012; Becker, 2019; Bird et al, 2005; Skala et al, 2007; Heikal, 2010; Sharick et al, 2018; Sanchez et al, 2018; Sanchez et al, 2019; Ma et al, 2019). It has been observed that the fraction of enzyme-bound NADH and NADH fluorescence lifetimes are correlated with the activity of oxidative phosphorylation, indicating that there is a connection between NADH enzyme-binding and mitochondrial metabolic fluxes (Bird et al, 2005; Skala et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of imaging has been adapted for bulk measurements by utilizing a plate reader 63 or for distinct objects by coupling it with a microscope. 64,65 By expanding this setup to multiphoton excitation on a microscope, phototoxicity of the sample is decreased and deeper penetration is possible for large tissue samples of up to 3 mm. 66 This technique can also be coupled with confocal imaging methods to measure cell morphological parameters or fluorescent markers of cell death.…”
Section: Main Text/sectionsmentioning
confidence: 99%